The Effects of Packaging, Digital Information, and Crowd Logistics on Last-Mile Delivery through Distribution Performance among Food and Beverage SMEs in Bandung - Irdhatullah Irdhatullah; Agus Purnomo; Melia Eka Lestiani (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study examines the effects of packaging, digital information, and crowd logistics on distribution performance and their implications for last-mile delivery among food and beverage SMEs utilizing online transportation services in Bandung, Indonesia. The rapid growth of digital-based delivery services has increased operational complexity in urban logistics, particularly regarding delivery accuracy, timeliness, and distribution effectiveness. A quantitative explanatory approach was employed using survey data collected from 131 SMEs selected through probability sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The findings reveal that packaging, digital information, and crowd logistics positively and significantly affect both distribution and last-mile delivery. In addition, distribution has a positive and significant effect on last-mile delivery performance. Mediation analysis further confirms that distribution partially mediates the relationships between packaging, digital information, crowd logistics, and last-mile delivery. These findings indicate that effective distribution systems strengthen the influence of operational, physical, and digital factors on final delivery performance. This study contributes to the logistics and supply chain literature by proposing an integrative framework that simultaneously combines packaging, digital information, and crowd-based logistics dimensions within a unified last-mile delivery model for online transportation-based SMEs.